The Mechanical Properties of 3D Printed CuZn28 Brass Specimens with Different Orientations - Szakál, Zoltán; Kári-Horváth, Attila; Pataki, Tamás; Odrobina, Miklós (International Journal of Engineering and Management Sciences, 2019)
In this paper, the properties of CuZn28 brass raw material were presented. The 3D printed metal specimens are made from this material with different orientations. Their mechanical properties (tensile strength, yield strength) and elongation were investigated according to MSZ EN 6892-1: 2012 standard. The strength of the different printing directions is analyzed and it is determined which printing direction is the most favourable. Finally, the effect of the different printing directions upon the structure of the material is studied.